Elastic wave velocity measurements of polycrystalline phase A (Mg7Si2O8(OH)6) at high pressures of subduction zone - Huong, Phan Thien (Vietnam Journal of Earth Sciences, 2012)
Ultrasonic wave propagation velocities of polycrystalline aggregates of phase A (Mg7Si2O8(OH)6), a dense hydrous magnesium silicate (DHMS) phase, has been measured in the pressure range from 1 to 11 GPa at room temperature. The combination of sol-gel and hot isostatic pressing techniques were employed to produce high quality specimens. Measurements were carried out in a 6/8 multi-anvil device using an ultrasonic wave propagation technique. A sin(x)/x signal was propagated through the rock sample and reflections were collected to measure the travel times that, in turn, were used to determine the wave propagation velocities. From the measured velocities, the elastic properties of phase A have been obtained by applying a third order Eulerian finite-strain equation of state resulting in KSo=100(1) GPa, K’S=6,3(1), G=61(1) GPa, and G’=2,2(1). Experiments are reproducible and confirm that we can measure elastic wave velocities of dense hydrous magnesium silicate minerals at pressures corresponding to the Earth´s upper mantle approaching transition zone pressure conditions in a multi-anvil apparatus.